GENERAL MODEL OF FORMING OF SYSTEM OF DEFENCE STATE INFORMATIVE RESOURCES - Юдин, О. К.; Бучик, С. С.; Фролов, О. В. (Science-based technologies, 2015)
The article deals with topical issues of protection of state informative resources in all areas of state policy of national security. The authors presented a general model of the system of protection of state informative resources in the form of structural and logical scheme on the basis of methodologies of “double triple protection”. A model is presented in composition three basic blocks: control system by informative security of state informative resources; directions of protection of state informative resources in the spheres of security; presentation of state informative resources as component of national safety. More in detail the first block (control system by informative security of state informative resources) is exposed taking into account to the basic stages of introduction of this system according to the international standards of series of ISO/IEC 2700x. Certain basic directions of further researches: determination of policy of security of state informative resources and introduction of control system by risks.